Safinamide as an adjunct to levodopa monotherapy in Asian patients with Parkinson’s disease experiencing early wearing-off: a pooled analysis of the J-SILVER and KEEP studies - Nishikawa, Noriko; Kwon, Do-Young; Kogo, Yuki; Hatano, Taku; Cho, Jin Whan; Kobayashi, Chizuru; Shiiba, Hiroyuki; Kim, JiEun; Ishida, Takayuki; Baik, Jong Sam; Hattori, Nobutaka (Frontiers in Neurology, 2025)
BackgroundLimited trials are evaluating the efficacy of monoamine oxidase B inhibitors as an adjunct to levodopa monotherapy for early wearing-off in Parkinson’s disease (PD). We evaluated the efficacy and safety of safinamide in patients with fluctuating PD treated with levodopa monotherapy.MethodsThis pooled analysis used data from the J-SILVER and KEEP studies and targeted patients with PD experiencing wearing-off who received safinamide as adjunct to levodopa monotherapy. Efficacy endpoints were mean changes in 39-item Parkinson’s Disease Questionnaire (PDQ-39), Movement Disorder Society-Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) Parts III and IV, and daily OFF time at 18 weeks of treatment.ResultsOf 54 patients (J-SILVER, N = 24; KEEP, N = 30), 41 completed the studies. Although not statistically significant, the change in PDQ-39 Summary Index exceeded the minimal clinical important difference (mean [standard deviation (SD)]: −2.2 [7.5], p = 0.094) at Week 18. Significant improvements in MDS-UPDRS Parts III and IV scores and daily OFF time were observed at Week 18 from baseline (mean [SD]: −2.8 [8.5]; p = 0.043, −1.3 [2.7]; p = 0.004, and −1.2 [3.5] hours; p = 0.041, respectively). Adverse events occurred in 24 patients (43.6%) and adverse drug reactions (ADRs) occurred in 12 patients (21.8%). ADRs with an incidence ≥5% were dyskinesia (3 events, 5.5%). In subgroup analyses, improvements in PDQ-39 Summary Index and MDS-UPDRS Parts III and IV were significant in patients aged ≥75 years (p = 0.039, p = 0.029, and p = 0.025, respectively).ConclusionSafinamide as an adjunct to levodopa monotherapy was effective for early wearing-off without any new tolerability concerns. Safinamide was particularly beneficial in elderly patients.